Palladium/Rhodium Cooperative Catalysis for the Production of Aryl Aldehydes and Their Deuterated Analogues Using the Water–Gas Shift Reaction. Issue 32 (17th July 2018) - Ibrahim, Malek Y. S.; Denmark, Scott E.
Abstract: A novel Pd/Rh dual‐metallic cooperative catalytic process has been developed to effect the reductive carbonylation of aryl halides in moderate to good yield. In this reaction, water is the hydride source, and CO serves both as the carbonyl source and the terminal reductant through the water–gas shift reaction. The catalytic generation of the Rh hydride allows for the selective formation of highly hindered aryl aldehydes that are inaccessible through previously reported reductive carbonylation protocols. Moreover, aldehydes with deuterated formyl groups can be efficiently and selectively synthesized using D2 O as a cost‐effective deuterium source without the need for presynthesizing the aldehyde. Abstract : The reductive carbonylation of aryl iodides using H2 O as the hydride source and CO as the carbonyl source as well as the terminal reductant has been accomplished by cooperative Pd/Rh catalysis. The cooperation between the two metals works optimally in the presence of 4, 4′‐dimethoxy‐2, 2′‐bipyridine as the ligand and tetramethylethylenediamine as the base to give valuable aldehydes.